Preprocedure Intravenous Recombinant Tissue Plasminogen Activator and Risk of Distal Embolization with Thrombectomy in Acute Ischemic Stroke - Qureshi, Adnan, I; Asif, Ahmer; Aytac, Emrah; Liaqat, Jahanzeb; Gurkas, Erdem; Lobanova, Iryna; French, Brandi R. (Elsevier, 2019)
Background: Intravenous recombinant tissue plasminogen activator (IV rt-PA) prior to thrombectomy may reduce the risk of intraprocedural distal embolization in acute ischemic stroke patients. Methods: We analyzed the diffusion-weighted imaging acquired with 1.5- or 3-T magnetic resonance imaging (MRI) scans obtained within 24 hours of thrombectomy in consecutive acute ischemic stroke patients. An independent physician identified distal embolization, defined as discrete foci of restricted diffusion independent of the primary area of infarction on MRI scan. Patients were stratified based on whether they had or did not receive IV rt-PA prior to thrombectomy. Results: Distal embolization was seen in 59 (ipsilateral in 56) of 63 patients (mean age +/- SD; 64.6 +/- 15.3 years) who underwent thrombectomy (mean number 8.6; range 0-32). There was no difference in mean number of ipsilateral hemispheric distal embolization between the 2 groups (7.9 +/- 6.1 versus 7.5 +/- 7.6, P = .82). After adjusting for age, admission National Institutes of Health Stroke Scale score, the time interval between symptom onset and thrombectomy, there was no association between receiving IV rt-PA prior to thrombectomy and number of ipsilateral distal emboli (P = .90). There was no relationship between the number of ipsilateral emboli and rates of favorable outcome after adjusting for other confounders (adjusted odds ratio 1.0; 95% confidence interval .89 - 1.0; P = .40). Conclusions: Although distal embolization is very common after thrombectomy, IV rt-PA prior to procedure does not reduce the risk of intraprocedural distal embolization.
Keywords: Thrombectomy; activase; recombinant tissue plasminogen activator; distal embolization; acute ischemic stroke; magnetic resonance imaging